Development of an Adaptive Learning Module Using Attributes of PowerPoint Show - Azhar, Habiba; Khanam, Afifa; Quraishi, Uzma (International Journal of Psychosocial Rehabilitation, 2020)
The present research is a type of research and development where researchers have prepared an adaptive learning module for subject of science, consisting 12 chapters, for 6th grade students in Pakistan using attributes of PowerPoint show. The module uses principles of adaptive content and adaptive assessment for personalized instruction. Taking all 6th grade students of District Lahore as the population of the study, the researchers selected three experimental and three control groups who were intact groups with, N =30 each, from three different schools of district Lahore. Total 180 students participated in the study. The module was assessed through a quasi-experimental, pre-test post-test experimental and control group design on three diverse groups of 6th grade science students; in the beginning, during and at the end of 6th grade year. The experimental groups showed a significantly higher gain score as compared to their competitive control groups. The module was refined in the light of findings and feedback of students during adaptive learning session. The study has implications for using such modules for reducing time span of learning, keeping students engaged and active, coping students’ individual pace and mastery of learning.